2010
DOI: 10.2215/cjn.03700410
|View full text |Cite
|
Sign up to set email alerts
|

Damned If You Do, Damned If You Don't

Abstract: Sodium polystyrene sulfonate (SPS) potassium binding resins increase colonic potassium excretion and are approved by the U.S. Food and Drug Administration (FDA) for the treatment of hyperkalemia. In 2009, the FDA recommended that sorbitol, a cathartic often given with SPS to prevent obstipation, not be added to SPS powder because of associated colonic necrosis. A premixed oral suspension of SPS in 33% sorbitol was not included in this warning. SPS resins increase stool potassium excretion in normokalemic subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
70
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 18 publications
0
70
0
2
Order By: Relevance
“…For example, diuretics are effective (16) but may be inappropriate for all patients because of volume control: in the present study, ,25% of patients with hyperkalemia at baseline were treated with loop or thiazide diuretics, suggesting that contraindications may exist for many patients. Likewise, sodium polystyrene sulfonate was a mainstay of management (17); however, its efficacy is questionable given the emerging safety concerns with its persistent use (18). Furthermore, our study results indicate that one frequent response to hyperkalemia was discontinuation of RAAS blockers.…”
Section: Discussionmentioning
confidence: 77%
“…For example, diuretics are effective (16) but may be inappropriate for all patients because of volume control: in the present study, ,25% of patients with hyperkalemia at baseline were treated with loop or thiazide diuretics, suggesting that contraindications may exist for many patients. Likewise, sodium polystyrene sulfonate was a mainstay of management (17); however, its efficacy is questionable given the emerging safety concerns with its persistent use (18). Furthermore, our study results indicate that one frequent response to hyperkalemia was discontinuation of RAAS blockers.…”
Section: Discussionmentioning
confidence: 77%
“…6,8 A study published in 2009 reported 11 cases of colonic necrosis associated with the use of sorbitol-SPS over the course of 9 years, 4 of which were fatal. 25 In the same year, the FDA posted warnings about the association between sorbitol-containing SPS and potentially fatal intestinal necrosis (bleeding, ischemic colitis, perforation).…”
Section: Discussionmentioning
confidence: 99%
“…7 SPS is predominantly used for mild hyperkalemia (defined as serum potassium between 5 and 6 mmol/L), where the risk of complications is low. 8 SPS was approved in 1958 by the US Food and Drug Administration (FDA), before drug manufacturers were required to prove that their products were efficacious. 7,9 SPS was approved in Canada 3 years later, in 1961.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium polystyrene sulfonate (Kayexalate) was approved in 1958 by the US FDA, as a potassium-binding resin in the colon, for the management of hyperkalemia. 1 Similarly, calcium resonium or calcium polystyrene sulfonate has been approved for use in Europe. The use of potassiumbinding resins has proven to be of value in the pre-dialysis chronic kidney disease (CKD) setting and in the management of emergency hyperkalemia; however, there is insufficient evidence regarding its efficacy and utility in patients with end-stage renal disease on dialysis.…”
Section: Introductionmentioning
confidence: 99%